Edukasi Deteksi Dini Stroke Pada Komunitas Diabetes Di Kota Mataram - Ilsa Hunaifi; Herpan Syafii Harahap; Joko Anggoro; I Gede Yasa Asmara; Rina Lestari; Dewi Suryani (Universitas Mataram, 2019)
Stroke remains one of the major causes of death and disability in Indonesia with a mortality and disability rate of 15% and 65%, respectively. Diabetes is known as a modifiable risk fator on stroke. Promptly identifying the symptoms of stroke is crucial as it leads to faster treatment and minimize brain damage. However, most patients are unaware of the early warning signs and symptoms of stroke. Therefore, providing education on early detection of stroke for patients with diabetes is essential as it may improve awareness on early signs of stroke hence allow patients to seek early treatment and later reduce the impact of the disease. The aim of this community education is to increase awareness of stroke and provide information on early signs and prevention of stroke among patients with diabetes.To achieve the aim of this community education include provide a talk/presentation on early sign of stroke and healthy life style for diabetes patient and evaluation of process. Evaluation of the community education was conducted through a pre and posttest to all participant on the related issue. Approximately 18 diabetes patients took part in this community education. The pre-test average score of participants was 73.33%. After providing education on stroke early detection, the participants' average score increased to 86.67 or increased by 18%. Education for early detection of stroke among Diabetes patients increased participants' understanding of the symptoms and early signs of stroke